NILAI PANCASILA DALAM PEMBAHARUAN HUKUM PIDANA - Andhie Fajar Arianto; Ludy Himawan (Universitas Muhammadiyah Jember, 2021)
Recent criminal law has been applied since 1946, passed in the law number 1 Year 1946 which is the legacy of European colonial era, and since the Indonesian independence has undergone rapprochement with the needs or requirements of an independent nation, even though the process has not been easy and through such a long thought-provoking throes between varied views of criminal law experts from time to time. How the renewal of national criminal law can be realized is the problem faced by the experts in law and politics in the legislative body which has not hitherto been passed yet. The latest issue about criminal law is not only related to the criminal matters, but also including criminal responsibility as well as ideal, humanistic and rational criminalization. Rather, how the reform of criminal law needs to promote the values contained in Pancasila thus the purpose of criminalization can be completely acceptable by the people.